THE PROTECTION OF JUVENILES IN A CRIMINAL PROCEEDINGS - Kovacević, Milica (Law - Theory and Practice, 2021)
In recent years a significant attention has been paid to the protection of juveniles in the context of a criminal procedure. It cannot be denied that the participation of juveniles in these proceedings could be the cause of secondary victimization and trauma. In addition, the specific position of the child established by the UN Convention on the Rights of the Child requires the minors to be allowed to actively participate in a criminal proceedings and to be adequately informed about various aspects and consequences of the procedure. The paper first gives a brief overview of the relevant international documents on the rights of juveniles in a criminal procedure, followed by the analysis of the domestic normative framework in the same field. A formal dogmatic approach has been applied. Afterwards, the author summarizes the state of the rights of minors in a criminal procedure in practice in Serbia. The aim of this paper is to point out the possible improvements of the position of juveniles in a criminal proceedings in Serbia.